2008
DOI: 10.1073/pnas.0810230105
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide signaling components in differentiation of embryonic stem cells into myocardial cells

Abstract: cardiomyogenesis ͉ cyclic GMP ͉ soluble guanylyl cyclase ͉ NO donors ͉ sGC activators E mbryonic stem (ES) cells are derived from the inner cell mass of the preimplantation embryo, and because of their selfrenewal and pluripotency, they are thought to revolutionize the field of regenerative medicine (1-3). Although transplantation of stem cells into animal models of cardiac injury and Parkinson's disease has revealed some beneficial effects, a better understanding of the role of specific signaling pathways inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 29 publications
(40 reference statements)
4
71
0
Order By: Relevance
“…In a recent study of human and mouse ESCs, NO donors and sGC activators could increase the mRNA expression of cardiacspecifi c genes myosin light chain and Nkx2.5, whereas NOS inhibitors decreased their mRNA expression [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study of human and mouse ESCs, NO donors and sGC activators could increase the mRNA expression of cardiacspecifi c genes myosin light chain and Nkx2.5, whereas NOS inhibitors decreased their mRNA expression [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this way, NO regulates diverse cellular processes in the cardiovascular, central nervous system, and immune system of the adult mammal. Several reports also suggest a role for NO signaling in cardiac differentiation [9][10][11][12]. Furthermore, defects in bicuspid aortic valves and atrial and ventricular septa are common in endothelial NOS (eNOS)-defi cient neonates [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies using ES cells indicate differential expression and function of various NO signaling components Mujoo et al, 2006) in ES and differentiated cells. Using activators of NO signaling pathway, we were able to show enhanced differentiation of both mouse and human ES cells with combination of nitric oxide donors (NO donors) and soluble guanylyl cyclase (NO receptor) activators compared to either of the two agents used separately (Mujoo et al, 2008). Nitric oxide mediates important physiological functions associated with integrative body systems including cardiovascular and nervous system, (Murad, 2006;Mujoo et al, 2011).…”
Section: Tablementioning
confidence: 96%
“…Furthermore, we have shown that both nitric oxide donors and soluble guanylyl cyclase (NO receptor) activators demonstrate enhanced differentiation of human and mouse embryonic stem cells and combined effects of these agents were additive. This was accompanied by robust induction in cGMP production compared with either of the two agents alone suggesting that NO-cGMP pathway plays a significant role in differentiation of stem cells (Mujoo et al, 2008).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation